2022
DOI: 10.4103/njms.njms_173_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of maxillofacial injuries and treatment outcome after bear attacks in Jharkhand population

Abstract: Introduction: Sloth bear, a native species of Indian subcontinent, has a population estimate of 1200–1500 in Jharkhand. Human habitats in proximity to forest reserve cause frequent human–bear interactions and thus bear attack injuries. Face is the most common site affected. This is a prospective study performed to evaluate the incidence and pattern of maxillofacial trauma after bear attack and the outcome of the treatment provided to them. Materials and Methods: Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Because of a bear attack, a person will receive multiple injuries, necessarily including the head [ 10 , 11 , 17 , 18 , 19 , 20 , 21 ]. The cranio-maxillofacial region is the most common and vulnerable site affected during a bear attack [ 12 ]. Thus, we found confirmation of the bloodthirstiness of bears in Robert Armitage Sterndale’s book “Mammalia of India” (1884) in the following description: “the victim being often terribly disfigured even if not killed, as the bear strikes at the head and face” [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of a bear attack, a person will receive multiple injuries, necessarily including the head [ 10 , 11 , 17 , 18 , 19 , 20 , 21 ]. The cranio-maxillofacial region is the most common and vulnerable site affected during a bear attack [ 12 ]. Thus, we found confirmation of the bloodthirstiness of bears in Robert Armitage Sterndale’s book “Mammalia of India” (1884) in the following description: “the victim being often terribly disfigured even if not killed, as the bear strikes at the head and face” [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45% of fractures of the facial bones include injuries to the mandible, 35% include injuries to the zygomatic bone, 20% include injuries to the maxilla, and 10% include injuries to the nasal bones [ 19 ]. According to Vishal et al (2022), the zygomatic orbital complex (66.6%), mandible (40%), and maxilla (27%) are most affected [ 12 ]. Research conducted in Nepal in 2015 showed that most of the victims had injuries to the facial bones, among which the zygomatic bone was injured more often than the others [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations